Potential for Phages in the Treatment of Bacterial Sexually Transmitted Infections - Kathryn Cater; Ryszard Międzybrodzki; Vera Morozova; Sławomir Letkiewicz; Marzanna Łusiak-Szelachowska; Justyna Rękas; Beata Weber-Dąbrowska; Andrzej Górski (Antibiotics, 2021)
Bacterial sexually transmitted infections (BSTIs) are becoming increasingly significant with the approach of a post-antibiotic era. While treatment options dwindle, the transmission of many notable BSTIs, including Neisseria gonorrhoeae, Chlamydia trachomatis, and Treponema pallidum, continues to increase. Bacteriophage therapy has been utilized in Poland, Russia and Georgia in the treatment of bacterial illnesses, but not in the treatment of bacterial sexually transmitted infections. With the ever-increasing likelihood of antibiotic resistance prevailing and the continuous transmission of BSTIs, alternative treatments must be explored. This paper discusses the potentiality and practicality of phage therapy to treat BSTIs, including Neisseria gonorrhoeae, Chlamydia trachomatis, Treponema pallidum, Streptococcus agalactiae, Haemophilus ducreyi, Calymmatobacterium granulomatis, Mycoplasma genitalium, Ureaplasma parvum, Ureaplasma urealyticum, Shigella flexneri and Shigella sonnei. The challenges associated with the potential for phage in treatments vary for each bacterial sexually transmitted infection. Phage availability, bacterial structure and bacterial growth may impact the potential success of future phage treatments. Additional research is needed before BSTIs can be successfully clinically treated with phage therapy or phage-derived enzymes.